Proceedings of the Twenty-Third Annual ACM-SIAM Symposium on Discrete Algorithms 2012
DOI: 10.1137/1.9781611973099.129
|View full text |Cite
|
Sign up to set email alerts
|

Rumor Spreading and Vertex Expansion

Abstract: We study the relation between the rate at which rumors spread throughout a graph and the vertex expansion of the graph. We consider the standard rumor spreading protocol where every node chooses a random neighbor in each round and the two nodes exchange the rumors they know. For any n-node graph with vertex expansion α, we show that this protocol spreads a rumor from a single node to all other nodes in O(α −1 log 2 n √ log n) rounds with high probability. Further, we construct graphs for which Ω(α −1 log 2 n) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Similar results were obtained for the spreading time of uniform gossip on networks with vertex expansion α. In particular, [14,13] proved an O( log 2 n α ) bound and showed it to be tight as well. These results demonstrate very nicely that uniform gossip performs at least as good as the worst bottleneck that can be found in the network.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained for the spreading time of uniform gossip on networks with vertex expansion α. In particular, [14,13] proved an O( log 2 n α ) bound and showed it to be tight as well. These results demonstrate very nicely that uniform gossip performs at least as good as the worst bottleneck that can be found in the network.…”
Section: Related Workmentioning
confidence: 93%
“…A series of results showed that this algorithm performs well on well-connected graphs with no bottleneck(s) [11,22,6,5,12,14,13]. More precisely, the main result is a tight bound of O( log n Φ ) rounds, where Φ is the conductance of the network.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the time required for randomized information spreading and the vertex expansion of the underlying graph was studied in [24,25,40]. Feige et al [17] showed in their important paper a bound of O(∆(D + log n)) rounds for UniformGossip to spread a rumor in a graph of diameter D and maximum degree ∆.…”
Section: Related Workmentioning
confidence: 99%
“…While usually good expansion of the underlying graph implies fast rumor spreading [3,5,6,19,21,34], it was far from clear if graph expansion is the only reason for fast rumor spreading and more general gossip processes. For instance, most of these gossip algorithms are inherently randomized, and all of the analysis of these algorithms crucially rely on choosing neighbors independently and uniformly at random in each round.…”
Section: Introductionmentioning
confidence: 99%